Data for Development DAC member priorities and challenges - Sanna, Valentina (OECD Development Co-operation Working Papers, 2017)
The 2030 Agenda for Sustainable Development commits the international community to support the modernisation and strengthening of national statistical capacities and systems in developing countries and to increase significantly the availability of high-quality, timely, reliable and disaggregated data to measure their progress against the Sustainable Development Goals. This paper, informed by a survey circulated among DAC members between February and April 2017, presents DAC members' policies and practices to support national statistical capacities and systems in developing countries. It highlights some of the main challenges that DAC members face in relation to making data work for sustainable development, notably in co-ordinating their support for statistics to avoid duplication and find synergies, in mobilising more resources, and in using quality data for development co-operation decision-making, programming, monitoring and reporting. The findings presented in this paper will inform the analysis of the 2017 Development Co-operation Report on Data for Development which will be published in October 2017. The report will provide guidance to providers of development assistance on how to best support developing countries to have and use quality and timely data for enabling delivery of the SDGs